Dopaminergic Neurones in the Main Olfactory Bulb: An Overview from an Electrophysiological Perspective - Pignatelli, Angela; Belluzzi, Ottorino (Frontiers in Neuroanatomy, 2017)
The olfactory bulb (OB), the first centre processing olfactory information, is characterised by a vigorous life-long activity-dependent plasticity responsible for a variety of odour-evoked behavioural responses. It hosts the more numerous group of dopaminergic (DA) neurones in the central nervous system, cells strategically positioned at the entry of the bulbar circuitry, directly in contact with the olfactory nerve terminals, which play a key role in odour processing and in the adaptation of the bulbar network to external conditions. Here, we focus mainly on the electrophysiological properties of DA interneurones, reviewing findings concerning their excitability profiles in adulthood and in different phases of adult neurogenesis. We also discuss dynamic changes of the DA interneurones related to environmental stimuli and their possible functional implications.